Psilocybin-Induced Neuroplasticity and Sustained Antidepressant Effects - Komarczewska, Anna Maria; Matusiak, Filip; Brzoza, Klaudia; Kociński, Michał; Iglewski, Patryk; Pietrasz, Michał (Quality in Sport, 2026)
Psilocybin-assisted interventions have shown rapid reductions in depressive symptoms in controlled clinical settings, raising questions about biological mechanisms supporting durability beyond the acute drug effect. [5,7] Mechanistic accounts increasingly focus on neuroplasticity as a candidate pathway linking transient serotonergic receptor activation to longer-lasting psychological and clinical change. [2,6] To synthesize evidence from the publications regarding (1) antidepressant clinical outcomes after psilocybin-assisted interventions and (2) neuroplasticity-related biological findings that plausibly support sustained improvement. [2,3] Narrative review using only (clinical trials/secondary analyses and mechanistic animal/neuroimaging work). Evidence was summarized qualitatively; no meta-analysis was performed. [2,16] Randomized and open-label clinical studies report rapid symptom reduction and follow-up persistence in major depression and cancer-related depression/anxiety, including six-month outcomes in treatment-resistant depression (TRD) protocols with psychological support. [4,5,7,19] Preclinical work provides convergent evidence of plasticity-relevant change after psilocybin, including structural synaptic remodeling in frontal cortex and hippocampal plasticity-related outcomes in extinction learning paradigms. [3,8] Human neuroimaging work reports changes consistent with altered large-scale brain dynamics after psilocybin and TRD-related mechanistic findings on fMRI. [6,20] Across the uploaded dataset, psilocybin-assisted therapy is associated with rapid antidepressant effects and durability signals in selected samples, while convergent animal and human mechanistic findings support neuroplasticity as a biologically plausible contributor to sustained clinical improvement. [2,3]